Using Stata for survey data analysis - Minot, Nicholas (International Food Policy Research Institute, 2009)
This manual was prepared to be used as part of a one-week training course. Earlier versions of the manual have been used in training courses in various countries. This manual describes how to use Stata to store, describe, and analyze data. The emphasis is on the analysis of household survey data, but Stata can be used with any database. It should be noted that this course is not a lecture course, but rather it is a semi-structured hands-on workshop in which trainees will use computers to learn different methods of analyzing data. Thus, active participation of the trainees is expected and necessary to maximize the benefit from the training. The training modules focus on how to use computer software to implement a wide range of topics and analytical methods. In order to cover this range of methods, the course cannot provide detailed explanations of the all statistical methods themselves, so it is assumed that trainees have some familiarity with statistical concepts.